A qualitative content analysis of e-strategies for Research, Innovation and Commercialization: A case of global bodies,Malaysian ministries and Research university. - Jano, Zanariah; Janor, Hawati; Mohd Jailani, Mohd Nor; Rabiah, Ahmad; Shaaban, Azizah (Springer, 2014)
Research, Innovation and Commercialization (R, I & C) are now widely accepted as critical tools to improve economy, eradicate poverty,and enhance human development. However, in a developing country like Malaysia, commercialization effort to date is quite modest with low number of research and innovation output from Malaysian universities on a national and international scale. Nowadays, communication and information are transmitted through Internet resources which acts as marketing tools for research,innovation, and commercialization to the global community. Recognizing these potentials, electronic strategies (e-strategies) encompassing R, I & C are on the rise across Asia. This chapter aims to analyze the trend of e-strategies in R, I & C of the global bodies, Malaysian Ministries and research university in Malaysia using a qualitative content analysis. The framework is based on the extant literature and consists of the dynamic cycle of Web resources namely the Web content, interactivity, navigation links, design infrastructures, assessment, and continous quality improvement (CQI). While the WIPO embraces and blends well with the potential advantages of e-strategies, the Scopus lacks few features about the organization and international networking,assessment, and CQI. The Ministries and the university are yet to adequately reflect truly comprehensive and integrated strategies for harnessing and exploiting these potentials in order to gear for internationalization and collaboration across countries.